Discord of Biological and Psychological Measures in a Group of Depressed African American and White Cancer Patients - Zhang, Amy Y. (Research Developments in Medicine and Medical Science Vol. 5, 2023)
Objective: This study examined racial differences in the self-report of depressive symptoms by reference to biological states. Methods: The study used a convenience sample of 20 depressed cancer patients (CES-D \(\ge\)16) (15 African Americans and 5 Whites). Subjects completed depression assessment on a battery of psychological measures and provided blood and saliva samples. Laboratory tests were performed on biomarkers (serotonin, cortisol and IL-6). T-test was computed to examine racial differences on biological and psychological measures. Results: Depressed Whites had a significantly higher cortisol level than depressed African Americans, but no significant group difference was found on any self-reported psychological measures of depression. There was a trend that African Americans reported fewer depressive symptoms on psychological measures but exceeded Whites on the domain of somatization; however, such group differences did not approach statistic significance in this small sample. Conclusion: African Americans did not appear to underreport depression in consideration of their biological states, but had a tendency to report more somatic symptoms than Whites; this may be attributable to non-depression diseases or reporting behavior rather than somatic sensitivity. African Americans exhibited more mistrust in the health care system, which could affect the self-report of depression. There is a discord between biological and psychological measures of depression. Biomarkers prove to be useful for evaluating racial difference in the self-report of depression. Implication for Nursing: Nurses should be cautious of somatic complaints when assessing African American cancer patient’s depression. Establishing trust is essential for an accurate assessment of depression in African American cancer patients.